2005
DOI: 10.3766/jaaa.16.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Ability of School Children with a History of Otitis Media to Understand Everyday Speech

Abstract: The present study compared the ability of school-aged children with and without a history of otitis media (OM) to understand everyday speech in noise using the University of Queensland Understanding of Everyday Speech Test (UQUEST). Participants were 484 children (246 boys, 238 girls) attending Grade 3 (272, mean age = 8.25 yr., SD = 0.43) and Grade 4 (212, mean age = 9.28 yr., SD = 0.41) at 19 primary schools in Brisbane metropolitan and Sunshine Coast schools. Children selected for inclusion were native spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
(26 reference statements)
1
13
0
6
Order By: Relevance
“…One might wonder why this is important when the sequelae of having a history of OME are not really apparent . However, as Keogh et al [2005] pointed out, although there were no statistically significant differences in mean speech understanding scores at a group level, there were large differences at the individual level as some children with a significant history of OM had very low speech understanding scores and require additional educational management. In addition, researchers, clinicians and teachers may wish to have a more complete understanding of how children with OM hear while they have the disorder.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…One might wonder why this is important when the sequelae of having a history of OME are not really apparent . However, as Keogh et al [2005] pointed out, although there were no statistically significant differences in mean speech understanding scores at a group level, there were large differences at the individual level as some children with a significant history of OM had very low speech understanding scores and require additional educational management. In addition, researchers, clinicians and teachers may wish to have a more complete understanding of how children with OM hear while they have the disorder.…”
mentioning
confidence: 91%
“…In the study by Keogh et al [2005], 484 children attending grade 3 (272, mean age = 8.25 years) and grade 4 (212, mean age = 9.28 years) at 19 primary schools in Brisbane metropolitan and Sunshine Coast schools were assessed for their ability to understand everyday speech using the University of Queensland Understanding of Everyday Speech Test (UQUEST) under 2 noisy conditions. The UQUEST is a computer-based test, intended to measure the understanding of everyday speech in the presence of noise by school children aged from 6 years.…”
mentioning
confidence: 99%
“…In a study of Keogh et al [2005], children were selected retrospectively based on the information reported by the parents in a parental questionnaire. Although the authors found a greater variation in the score of the OM group, performance on SPiN perception did not differ significantly from children without an OM history.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of recurrent OME (ROME) on hearing acuity in the short and long terms are well documented (6,7) . However, results on the auditory central nervous system (ANCS), despite the vast amount of information available, are controversial (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Studies focus on the premise of interdependence between episodes of OME and the change in tone thresholds, called fluctuating conductive hearing loss, because 80% children diagnosed with OME exhibit this kind of loss that acts as a sensory deprivation (8,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Other aspects to be considered that may have caused the divergent results are the variety of tests used and auditory abilities evaluated, as well as the age at which children were evaluated. Speech recognition in monotonic, low redundancy condition is commonly used, and the speech-in-noise test is the most studied (7,11,12,14) . However, temporal processing is also often chosen, represented by resolution abilities (2,10,16) as well as binaural interaction (7,8) .…”
Section: Introductionmentioning
confidence: 99%